Challenges, burden and emotional impact on Portuguese athletes during COVID-19 pandemic - Oliveira, Sara (2022)
This study aimed to explore how contextual variables associated with the period of confinement during pandemic can differentiate symptoms of anxiety, depression, and stress. It also intended to understand the concerns that were experienced by athletes when resuming their sport practice and how these could be associated withpsychopathological indicators. The sample comprised 265 athletes who completed self-reported questionnaires. Results demonstrated that there were differences in psychopathological indicators in terms of hours of training per week, and the type of contact that athletes have with their coach. Athletes reported concerns regarding the resumption of sport practice, and that were associated with anxiety, depression, and stress symptoms. This study may contribute in warning the sports community about the impact of contextual variables-related to critical moments of this pandemic. Sports communities should encourage the preservation of the athlete’s physical activities, as well as supporting coaches in continuing to guide athlete’s training.